Immunochemical study of a Paracoccidioides brasiliensis polysaccharide-like antigen - Mendes-Giannini, Maria José Soares [UNESP]; Toscano, E. [UNESP]; Del Negro, G. B. [UNESP]; Assis, C. M. [UNESP]; Garcia, N. M. [UNESP] (Oxford University Press (OUP), 1995)
The polysaccharide antigen from P. brasiliensis has been largely employed in serologic tests, as well as in skin tests, to evaluate cellular immunity. SDS-PAGE analysis of this antigen has revealed a variability in the number of bands exhibited by isolates SN, 265, 339, 113 and 18 (7 to 16 bands). The antigens obtained from isolates 2, PTL, 192 and Adel showed two or three bands. Glycoprotein analysis demonstrated a broad region between 50 and 90 kDa. Major bands of 48 and 30 kDa were present in almost all antigens. Optimal complement fixing dilution appears to be unaffected by the number of bands presented by different antigens. The immunoblot analysis revealed that the 90 and 30 kDa bands were mainly recognized by sera from paracoccidioidomycosis patients. Bands of high molecular weight were also recognized by most of the sera studied. Sera from histoplasmosis recognized the 94 kDa band. In conclusion, although the isolates exhibit quantitative variability in the number of fractions, it is possible to use only one or two samples given the greatest frequency of reactivity is seen in the 30 and 90 kDa fractions.
Keywords: immunoglobulin g; polysaccharide; controlled study; immunoblotting; immunochemistry; nonhuman; paracoccidioides brasiliensis; serodiagnosis; south american blastomycosis; Antigens, Fungal; Carbohydrates; Complement Fixation Tests; Electrophoresis, Polyacrylamide Gel; Humans; Immunoblotting; Paracoccidioides; Paracoccidioidomycosis; Proteins; Species Specificity